(untitled) (Research, Society and Development, 2021)
For Brazil, eight species names known as boldo were obtained in the literature, almost all with medicinal functions related to stomach and liver. The work aimed to present morphological diagnoses for the species known as boldo, grown in Brazil, as well as a key for identification, figures, taxonomic and medicinal comments. The morphological study was based on five fertile boldo collects in the municipality of Alta Floresta, Mato Grosso, and 47 exsiccates digitized in online databases, from collects carried out in Brazil, totaling 52 samples examined. The diagnoses were made from vegetative and reproductive traits at the Plant Morphology Laboratory, at the Herbário da Amazônia Meridional (UNEMAT). Three species of boldo are grown in Brazil, with medicinal uses related to the stomach and liver: Gymnanthemum amygdalinum (Delile) Sch.Bip. ex Walp., Plectranthus barbatus Andr. and Plectranthus neochilus Schltr., differentiated in terms of phyllotaxis, blade shape and leaf margins, coloration of glandular trichomes, types of inflorescences and densification between flowers in anthesis. Specimens determined in herbariums such as Plectranthus ornatus Codd do not correspond to the species, but P. neochilus, due to the size of the corolla that does not exceed 2 cm in length. Plectranthus amboinicus (Lour.) Spreng. it was not considered as boldo because it has no uses related to the stomach and liver, nor known in traditional literature as boldo. With the use of plant morphology, taxonomic reviews, e-taxonomy and references of medicinal plants it was possible to present the species popularly called boldo in Brazil and with valid scientific names, as well as to question species with dubious occurrence and popular name.